2021
DOI: 10.3390/microorganisms9091819
|View full text |Cite
|
Sign up to set email alerts
|

Tailed Lytic Bacteriophages of Soft Rot Pectobacteriaceae

Abstract: The study of the ecological and evolutionary traits of Soft Rot Pectobacteriaceae (SRP) comprising genera Pectobacterium and Dickeya often involves bacterial viruses (bacteriophages). Bacteriophages are considered to be a prospective tool for the ecologically safe and highly specific protection of plants and harvests from bacterial diseases. Information concerning bacteriophages has been growing rapidly in recent years, and this has included new genomics-based principles of taxonomic distribution. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 196 publications
(270 reference statements)
0
10
0
Order By: Relevance
“…The structures of Autographiviridae phages belonging to different taxa have much in common [86]. Meanwhile, the genome analysis of Autographiviridae phages showed that the majority of protein sequences differ substantially, except for the terminase large subunit (TerL) and major capsid protein, which are more conservative [86]. Comparison of the TerL amino acid sequences of Enterobacter phage KKP 3263 with Autographiviridae phages is presented in Figure 7.…”
Section: Analysis Of Phage Genomesmentioning
confidence: 99%
“…The structures of Autographiviridae phages belonging to different taxa have much in common [86]. Meanwhile, the genome analysis of Autographiviridae phages showed that the majority of protein sequences differ substantially, except for the terminase large subunit (TerL) and major capsid protein, which are more conservative [86]. Comparison of the TerL amino acid sequences of Enterobacter phage KKP 3263 with Autographiviridae phages is presented in Figure 7.…”
Section: Analysis Of Phage Genomesmentioning
confidence: 99%
“…The dominance, in the environment, of one, or few, genera of phages infective to a certain bacterial host species has been reported previously. Recent examples relevant to agriculture are the prevalence of Limestoneviruses among phages infecting potato pathogen Dickeya solani [ 82 , 83 ], and Ficleduoviruses among phages of aquaculture pathogen Flavobacterium columnare [ 84 ]. The accumulation of statistically robust data on available phage diversity either takes decades (as for E. coli or Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of the interactions between P. brasiliense F152 and PP99, a representative of the genus Zindervirus, has exhibited that the tail spike protein of this phage, gp55, deacetylated the side chain talose residue of bacterial OPS, providing the selective attachment of the phage to the cell surface (Lukianova et al, 2020). The morphology of another phage, namely PP35, is typical of the Ackermannviridae family, with a fairly long contractile tail about 120-140 nm, larger genome size and the presence of more open reading frames compared to the family Autographiviridae (Miroshnikov et al, 2021;Table 4) restricted to Dickeya strains (Day et al, 2017;Kabanova et al, 2019;Petrzik et al, 2021). The interaction of this phage with D. solani F012 has revealed that PP35 can depolymerize the OPS by its tail spike protein gp156 (Kabanova et al, 2019).…”
Section: Phag E-bac Teri Um Inter Ac Ti On Smentioning
confidence: 99%
“…This mechanism is mediated by phage tail spike proteins, which have enzymatic domains that degrade or modify the OPSs on the surface of the bacteria. This allows the phage to attach to the bacterial cell and subsequently inject its DNA inside the bacterium (Miroshnikov et al, 2021). The control and prevention of bacterial diseases requires precise differentiation of Pectobacterium and Dickeya species.…”
Section: Introductionmentioning
confidence: 99%